Laparoscopic totally extra peritoneal (TEP) inguinal hernia repair: A series of 47 cases - Shrestha, Suman Kumar (Journal of Kathmandu Medical College, 2017)
Background: Over the past years, several surgical techniques have been evolved, among which total extraperitoneal inguinal hernia repair is the laparoscopic technique which is more popular now. Objective: To evaluate the outcome of totally extra peritoneal laparoscopic hernioplasty in terms of operation time, hospital stay and complications. Methods: The prospectively designed descriptive study was carried out at Department of Surgery Unit III, Kathmandu Medical College Teaching Hospital from February 2014 to April 2015. Forty seven consecutive patients above 15 years of age underwent totally extra peritoneal repairs for inguinal hernias. The selection criteria were reducible primary or recurrent, unilateral, direct and indirect inguinal hernias. All the relevant details of each patient were noted subsequently and analyzed statistically using Statistical Program for Social Sciences (SPSS) version 15. Results: The mean age of patient was 49±2.5 years. The mean operation time was 65±5.3 minutes. There were no serious complications except four (8.5%) cases of groin seroma which resolved after single time aspiration. Three (6.3%) cases had developed recurrence, two (4.2%) had developed hydrocele in a median follow up period of 6±1.5 (range, 3-9months). The mean inpatient hospital stay was 1.7±0.2 (range, 1-2.4days). Conclusion: Total extra peritoneal hernioplasty is safe and feasible with acceptable complications and recurrence rates. Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, page: 120-123